UBE2J1 knockdown promotes cell apoptosis in endometrial cancer via regulating PI3K/AKT and MDM2/p53 signaling - Zhang Ping; Guo Huiping; Zhao Fang; Jia Ke; Yang Fei; Liu Xiaoli (Open Medicine, 2023)
Emerging evidence has demonstrated that ubiquitin conjugating enzyme E2 J1 (UBE2J1) exerts pivotal function in many cancers. UBE2J1 was reported to be dysregulated in endometrial cancer (EC). This study was designed to further investigate the regulatory character and mechanism of UBE2J1 in EC. Bioinformatic tools and databases were used to analyze gene expression pattern and gene expression correlation in EC tissues, and the prognosis of EC patients. Gene expression was evaluated by reverse-transcription quantitative polymerase chain reaction. Western blot was used for protein level detection. In vitro cell apoptosis was detected by flow cytometry analyses and TUNEL assays. In vivo cell apoptosis was evaluated by detecting Bax and Bcl-2 expression in tumor tissues via immunohistochemical and western blot analyses. In this study, UBE2J1 knockdown promoted cell apoptosis in EC cells and in mouse models of EC. PI3K and AKT expression is positively correlated with UBE2J1 level and is related to poor prognosis of EC patients. UBE2J1 knockdown repressed the PI3K/AKT pathway both in vitro and in vivo. UBE2J1 downregulation decreased MDM2 expression, but increased p53 expression. MDM2 overexpression reverses the promotion of UBE2J1 knockdown on cell apoptosis in EC. Overall, UBE2J1 knockdown induces cell apoptosis in EC by inactivating the PI3K/AKT signaling and suppressing the MDM2/p53 signaling.